A method for high-accuracy localization of microseismic sources in mines based on finite element simulation - Dianyan NING; KaiPeng ZHU; Yongsheng ZHU; Shuxia YUAN; Zhenfang ZHOU (Meitian dizhi yu kantan)
Objective and Methods Microseismic monitoring technology for mines can reflect the deformations and failure of rock layers by capturing low-frequency vibration signals their internal structure generated during the stress-induced deformation and failure of them. Accordingly, water inrush warnings and geologic hazard prediction can be achieved. Acoustic source localization, allowing for the localization of energy release and the early warning of potential hazards, plays a key role in this technology. Presently, when used for acoustic source localization, the time difference of arrival (TDOA) method is facing issues including high algorithmic complexity, significant impacts of probe arrangement on the localization accuracy, and low adaptability to complex stratigraphic structures. Using the finite element method, this study simulated the elastic wave propagation in various stratigraphic structures. Considering the transmission, reflection, and diffraction effects at various stratigraphic boundaries, this study investigated the impacts of various inversion models and probe arrangements on the localization accuracy. Results and Conclusions The results indicate that the point source control models can effectively simulate the elastic wave propagation in rocks, with the orthogonal probe arrangement delivering superior performance in the acoustic source localization. In planar homogeneous materials, compared to the probe sets arranged in double triangles, the probe sets arranged in a single square exhibited a decrease of 0.6% in the localization error, while probe sets arranged in double squares displayed an increase of 1.69% in the localization accuracy. In a planar layered structure, compared to uniform velocity inversion, the transmission inversion increased the localization accuracy by 15% in the case of probe sets with a double triangle arrangement and by 14.9% for a probe set with a double square arrangement. In a three-dimensional layered structure, compared to uniform velocity inversion, the transmission inversion increased the localization accuracy by 14.5% in the case of the probe set arranged in a trirectangular tetrahedron. Overall, the inversion method produces more significant impacts on the localization accuracy than the probe arrangement, and the proposed numerical method enables high-accuracy, rapid acoustic source localization using the TDOA method and transmission inversion. The results of this study provide a valuable reference for optimizing microseismic monitoring and early warning systems for mines.